Optimalisasi Penggunaan Canva dalam Pembelajaran Pendidikan Pancasila Yang Adaptif Dan Responsif Untuk Memenuhi Kebutuhan Siswa - Eduk, Veni Soraida; Iswahyudi, Didik; Zuhriyah, Luluk Masruroh (Universitas Muhammadiyah Ponorogo, 2026)
This study explores how the Canva application transforms of Pancasila Education learning at Celaket 21 Catholic Junior High School Malang into an adaptive and responsive experience. Researchers use a qualitative descriptive approach with case studies to collect data through in-depth interviews, participatory observation, and document analysis. They select informants using purposive sampling and analyze data using the Miles and Huberman model with triangulation for validity. Teachers actively integrate Canva to create engaging lessons, accommodate diverse learning styles, and empower students as content creators. Their motivation, easy access to Canva, premium belajar.id accounts, school infrastructure, and professional support drive the success of this implementation. Despite its effectiveness, technical limitations and varying levels of digital literacy among teachers remain challenges. Students express positive feedback, showing increased interest, active participation, and improved comprehension through visualization. Canva enhances 21st-century skills and strengthens civic values, aligning with the Merdeka curriculum. This study urges educators to enhance their digital competence, improve school infrastructure, and implement policies that support educational technology innovation.